PKM Promoting Virtual Da'wah for Prosperity of the Mosque-based Youth Activities - Abu Khaer; Aisyatul Humairo; Isyti Rozanah; Ika Maziyyatus Sholihah; Viatul Karimah; Moh. Jalaluddin; Muh Dzikri Izzabillah (GUYUB: Journal of Community Engagement, 2021)
Da'wah cannot be left from the mosque's existence as a center of worship and scientific development. The transformation of the use of digital media has penetrated various communication needs, including a strategy in virtual preaching by utilizing social media. Da'wah is no longer carried out by groups considered qualified in religious understanding, but every individual can do this virtual da'wah. Within the framework of the prosperity of the mosque, the Youth of the Mosque Baitissalam Paiton, Probolinggo started to use social media to spread positive religious values. It has not been accompanied by an awareness of the importance of concepts and strategies that are strong in the persuasive messages of virtual da'wah, so they need reinforcements. This method of community service is carried out by strengthening the concept of virtual da'wah, mosque youth branding, and audio-visual training to create interesting social media creative content attention of millennial youth. The results of community service activities show awareness social media to design a virtual da'wah strategy through creative social media content andincreased creativity in determining ideas to spread religious values for teenagers.